Dynamics in the soil, weed control and selectivity of sulfentrazone for eucalyptus - Carbonari, Caio Antonio [UNESP] (2020)
Weed control and selectivity of sulfentrazone for eucalyptus is directly related to its dynamics in the soil in different application modes. The objective of this work was to evaluate the dynamics of sulfentrazone applied at different rates, in different soil types, and with different application modes, the weed control, and the injuries to eucalyptus plants of different clones. Field experiments were conducted in Itatinga and in Paranapanema, in the state of São Paulo, Brazil, on sandy and clayey soils, respectively. The different sulfrentrazone rates (300 and 400 g ha-1 - sandy soil and 500 and 600 g ha-1 - clayey soil) were applied before and after subsoiling of the planting row in total area. Sulfrentrazone contents were quantified in soil samples of the 0-20 and 20-40 cm layers in the planting row and inter-row, using a Liquid Chromatography Mass/Mass (LC-MS/MS) system. Injuries on the eucalyptus plants and weed control were also evaluated. The sulfrentrazone contents in the soil were proportional to the applied rates, regardless of the soil, in the 27 and 70 DAA (days after application) (clayey) and 16 and 48 DAA (sandy) evaluations. In the first evaluations, the application of sulfentrazone before subsoiling resulted in a lower content of this herbicide in the planting row, compared to the application after subsoiling, but the contents were similar in the last evaluations (109 and 140 DAA). Weed control by the herbicide at the higher rates was better in the sandy soil (400 g ha-1) than in the clayey soil (600 g ha-1). No injuries to the tested Eucalyptus grandis clones (SF, SP1048, SP1049 and SP0791) were found under the study conditions. The sulfrentrazone dynamics is initially affected by the application mode, but it does not affect its weed control and selectivity for eucalyptus.